Why employment relations matter - Keith Sisson (University of Warwick, Industrial Relations Research Unit, 2010)
This paper has its origins in an on-going project labeled Employment Relations Matters. The title captures the double intention: to demonstrate the ways in which employment relations matters and to bring people up to date with the matters that the subject deals with. It is one of three in IRRU's Warwick Papers in Industrial Relations series covering the project's main themes. The two already published deal respectively with the nature of the employment relationship and the significance of institutions in its conduct. The present paper is concerned with the project's first intention, focusing on why employment relations matter in practice
Keywords: 330; Arbeitsbeziehungen; Industriesoziologie; Europa